2016
DOI: 10.1038/srep27971
|View full text |Cite
|
Sign up to set email alerts
|

The thermal and electrical properties of the promising semiconductor MXene Hf2CO2

Abstract: With the growing interest in low dimensional materials, MXenes have also attracted considerable attention recently. In this work, the thermal and electrical properties of oxygen-functionalized M2CO2 (M = Ti, Zr, Hf) MXenes are investigated using first-principles calculations. Hf2CO2 is determined to exhibit a thermal conductivity better than MoS2 and phosphorene. The room-temperature thermal conductivity along the armchair direction is determined to be 86.25~131.2 Wm−1 K−1 with a flake length of 5~100 μm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 67 publications
9
129
1
Order By: Relevance
“…along the armchair (zigzag) flake length of 1-100µm [55]. Among Sc 2 CT 2 (T= F, O, OH), Sc 2 C(OH) 2 is predicted to be a candidate for thermoelectric application at elevated temperatures more than 300 K due to a relatively good Seebeck coefficient, high electrical conductivity, and very low lattice thermal conductivity [53].…”
Section: Energy Conversion: Thermoelectric Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…along the armchair (zigzag) flake length of 1-100µm [55]. Among Sc 2 CT 2 (T= F, O, OH), Sc 2 C(OH) 2 is predicted to be a candidate for thermoelectric application at elevated temperatures more than 300 K due to a relatively good Seebeck coefficient, high electrical conductivity, and very low lattice thermal conductivity [53].…”
Section: Energy Conversion: Thermoelectric Devicesmentioning
confidence: 99%
“…Theoretically, many applications have been proposed for MXenes in electronic [39][40][41][42][43], magnetic [44][45][46][47][48], optical [49,50], thermoelectric [51][52][53][54][55][56], and sensing devices [57], as well as being new potential materials for catalytic and photocatalytic reactions [58][59][60][61][62][63], hydrogen storage media [64,65], and nanoscale superconductivity [66]. Some of MXenes are predicted to be topological insulators with large band gaps involving only d orbitals [67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Similar to graphene and BN, two dimensional MXenes have good physical properties, such as mechanical strength, electrical conductivity and thermal conductivity. [23][24][25][26][27][28] Some previous studies have reported the incorporation of MXenes (Ti 3 C 2 T x ) into different polymer matrices, such as ultrahigh-molecular polyethylene (UMWPE), polypyrrole (PPy), and polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
“…[106] The thickness difference of Ti 3 C 2 T x flakes leads to different resistances and transmittances; therefore, their optoelectronic properties are interesting. Moreover, the performance of the MXenes can be improved by making peculiar morphologies (e.g., hollow MXenes [121] ), changing the local structure of MXenes (e.g., doping by other atoms [122,123] ), modifying surfaces (e.g., heat treatment [38] ), increasing the MXene layer spacing (e.g., inserting cations or organic molecules [48,124] ), etc. [107,108] It is well known that titanium hydroxide and/or titania show good photocatalytic activities.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[52,53] Moreover, MXenes have demonstrated massive storage power with intercalated polyvalent cations, for instance, Ca 2+ ions, [54] Mg 2+ ions, [55,56] and Al 3+ ions. [38] The composites prepared by combining MXenes with different types of materials (e.g., stable carbon materials [57,58] ) are worth digging into to potentially improve their performances. [38] The composites prepared by combining MXenes with different types of materials (e.g., stable carbon materials [57,58] ) are worth digging into to potentially improve their performances.…”
Section: Introductionmentioning
confidence: 99%